The List Set Generator: A Construct For Evaluating Set Expressions - Shapiro, Stuart C. (University of Wisconsin-Madison Department of Computer Sciences, 1970)
The list set generator is defined and algorithms for its use are given. The list set generator is a construct which may be added to a list processing system or any system that handles sets. It efficiently generates the set which results from any expression involving sets and set operators. The efficiency derives from evaluating the expression as a whole and in parallel, rather than evaluating subexpressions and then using those sets to arrive at the final result.